2005
DOI: 10.1111/j.1368-5031.2005.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain-relieving factors in migraine and tension-type headache

Abstract: We performed the present study to compare patients with migraine and tension-type headache (TTH) in their behaviour during the attacks and the manoeuvres to relieve the pain. One hundred thirty consecutive patients with either migraine (n = 75) or TTH (n = 55) were questioned (including the use of a checklist) concerning their usual behaviour during the attacks and non-pharmacological manoeuvres performed to relieve the pain. The results of the two types of headache were compared. Patients with migraine tended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…However, excess sleep or sleep deprivation are thought to initiate migraine attacks. 1,12,13,17 The aspect of family history of migraine in the Kurdish population has not been previously explored. This factor was elaborated in the current studied population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, excess sleep or sleep deprivation are thought to initiate migraine attacks. 1,12,13,17 The aspect of family history of migraine in the Kurdish population has not been previously explored. This factor was elaborated in the current studied population.…”
Section: Discussionmentioning
confidence: 98%
“…1 Patients with migraine tended to perform few maneuvers to relieve the headache which include pressing and applying cold stimuli to the painful site, going to sleep, changing posture, sitting or reclining in bed (using more pillows than usual to lay down), isolating themselves, using symptomatic medication, inducing vomiting, changing diet and becoming immobile during the attacks. 13 This study discusses some of the triggering factors of migraine headache and their percentage in 200 Iraqi Kurdish patients including physical activity, psychological upset, menses, specific food and or drinks, changes in weather, lights, contraceptive pills and pregnancy, smells such as smoke or odors particularly perfumes and gasoline, and this study also intends to determine the effect of Ramadan fasting on migraines. This study also focuses on the most common medical and nonmedical relieving factors for migraine headache in the studied population, in addition to the estimation of the percentage of family history in Kurdish population.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for increased sleep need among migraineurs is migraineurs’ attempt to sleep for relieving migraine attacks. Migraineurs often report relieving migraine symptoms by sleep [27, 28]. Therefore, migraineurs may need longer sleep time than non-migraineurs for relieving their migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that simultaneous pressure of heat and cold reduced the headache's duration (7). Today, some patients report that they treat their headache using physical therapies, including cold application (5,810). Self-administered pain relief manoeuvres have been investigated in primary headache patients.…”
Section: Introductionmentioning
confidence: 99%